CULICIDS WITH MEDICAL AND VETERINARY RELEVANCE IN JUTIAPA, GUATEMALA: 2009-2017 - Rodríguez-Flores, Jaime (2018)
Th e objective of the investigation was to report the species of culicids registered in the Department of Jutiapa, Guatemalaassociated with bio-ecological aspects between 2009 and 2017. A retrospective–descriptive study was carried out througha documental review of the sample register of the Departmental Laboratory of Entomology of Jutiapa. Th is informationis the result of inspections made inside and around domiciles three times per year in 100% of the urban and rural areasthat include houses, vacant lots and natural breeding grounds. Seven genera with 17 species were collected. Aedes aegypti(Linnaeus, 1762), Aedes albopictus (Skuse, 1824) and Culex quinquefasciatus (Say, 1823) had the widest distribution. ElAdelanto and Moyuta as well as Agua Blanca, Atescatempa and Santa Catarina Mita were the municipalities with thehighest variety of species. Uranotaenia sapphirina (Osten Sacken, 1868) was registered as a new species in the Department.